Situation Report: Romania, 1 July 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Maurer's Exposition of the 1966-1970 Economic Plan Romanian-Burmese Communiqué Reaction to US Bombing of Hanoi and Haiphong Light Industry Development in Romania